Participação dos receptores purinérgicos do núcleo parabraquial lateral nas respostas cardiorrespiratórias induzidas pela hipóxia aguda e hipóxia crônica intermitente - Menezes, Miguel Furtado (Universidade Federal de São Carlos, 2015)
The lateral parabrachial nucleus (LPBN) is an important area of the hindbrain circuitry involved in cardiorespiratory control. Adenosine triphosphate (ATP) is considered an important central neurotransmitter and purinergic receptors are present in the LPBN. The involvement of purinergic mechanisms of the LPBN in the cardiorespiratory control during hypoxia is still unknown. In the present study, we investigated the effects of alpha, beta-me ATP (P2X purinergic agonist) alone or combined with PPADS (P2 purinergic receptor antagonist) injected into the LPBN on cardiorespiratory responses induced by acute hypoxia (7% O2 for 60 min) in unanesthetized rats and chronic intermittent hypoxia (CIH) (10% O2, 8 hours/7 days) in anesthetized rats. Additionally, in another unanesthetized rats group, we investigated the effect of acute hypoxia (7% O2 for 60 minutes) on the activity of LPBN neurons and also the effect of alpha, beta-me ATP injected into the LPBN on Fos immunoreactivity at NTS induced by acute hypoxia (7% O2 for 60 min). In unanesthetized group, we used male Holtzman rats (290-310 g, n=8/group) with stainless steel cannulas implanted bilaterally into the LPBN. A polyethylene tubing was inserted into abdominal aorta through femoral artery for recording mean arterial pressure (MAP) and heart rate (HR). Respiratory frequency (fR), tidal volume (VT) and ventilation (VE) were recorded by whole-body plethysmography. The unanesthetized rats received bilateral injections of PPADS (4 nmol/0.2 μL) into the LPBN 10 minutes before injections of alpha, beta-me ATP (2 nmol/0.2 μL) or saline into the LPBN. Ten minutes after the LPBN injections, a hypoxic gas mixture (7% O2) was ventilated in the chamber for 60 minutes. In anesthetized group, we used Sprague Dawley rats (300-400 g, n=7) were exposed for 7 days to CIH (alternating 6 min periods of 10% O2 and 4 min of 21% O2 from 8 am to 4 pm; and continuous exposition to normoxic at 21% O2 from 4 pm to 8 am). Mean arterial pressure (MAP), heart rate (HR), renal sympathetic nerve discharge (RSND) and amplitude and phrequency of phrenic nerve activity (PNA) were recorded in rats anesthetized with urethane and alpha chloralose, vagotomized and mechanically ventilated. The anesthetized rats received a unilateral injections of alpha, beta-me ATP (2.0 nmol/50 nL) before, 10 and 30 minutes after PPADS (0.125 nmol/50 nL) into the LPBN. For immunohistochemistry group we used male Holtzman rats, we studied the expression of Fos in the LPBN and medial parabrachial nucleus (MPBN) of unanesthetized rats exposed to 1 h of acute hypoxia, on another group, the animals received a bilateral injections of alpha, beta-me ATP into the LPBN or saline 10 minutes (n= 5/group) before the acute hypoxia for 1 h. After this period, the rats were deeply anesthetized and perfused to remove the brains and carrying out immunohistochemical procedures. In unanesthetized rats, bilateral injections of alpha,beta-me ATP into the LPBN potentiated acute hypoxia-induced increase in VT (= 4.0±0.3 mL/kg, vs. saline 2.2±0.2 mL/kg, or 81% of increase, p= 0.005) and VE (= 871±55 mL/kg/min, vs. saline: 598±60 ml/kg/min, or 45% of increase, p= 0.009), without changing hypoxia-induced tachypnea (fR = 49±5 cpm, vs. saline: 48±5 cpm). The pre-treatment with PPADS into the LPBN abolished the responses produced by alpha, beta-me ATP. Bilateral injections of alpha,beta-me ATP into the LPBN did not affect the hypotension, and tachycardia induced by acute hypoxia. In normoxic anesthetized rats, unilateral injections of alpha, beta-me ATP (2.0 nmol/50 nL) into the LPBN increased MAP (Δ = 10±2 mmHg, vs. saline: 0±1 mmHg, p<0.05), RSND (Δ = 40±12%, vs. saline: 1±1%) and phrequency PNA (Δ = 17±5 cpm, vs. saline: 0±1 cpm, p<0.05), without changing HR and amplitude PNA. Unilateral injection of PPADS into the LPBN abolished the increase in MAP (Δ = 0±1 mmHg), RSND (Δ = 3±3.1%) and phrequency PNA (Δ = 1±1 cpm) produced by alpha, beta-me ATP injected into LPBN. In anesthetized CIH rats, the injection of alpha, beta-me ATP into the LPBN increased even more MAP (Δ = 20±2, vs. saline: -1±1 mmHg), HR (Δ = 25±5 bpm, vs. saline: -1±1 bpm) and amplitude PNA (Δ = 87±31%, vs. saline: 2±1%), in addition to have increased also frequency PNA (Δ = 17±5 cpm, vs. saline: -1±1 cpm). In immunohistochemistry group the acute hypoxia produces activation of the LPBN neurons (93 ± 8, vs. normoxic 22 ± 8 cells), while the injection of alpha, beta-me ATP into the LPBN potentiated the Fos expression in caudal NTS (NTSc; 88 ± 4, vs. saline: 42 ± 8 cells) and rostral NTS (NTSr, 62 ± 8, vs. saline: 38 ± 4 cells). In conclusion, our data suggest that the P2 receptors into the LPBN are involved in the cardiorespiratory responses induced by acute hypoxia and chronic intermittent hypoxia and these responses activate neurons in the NTS, suggesting possible direct or indirect projections between the LPBN and the NTS.
Keywords: Fisiologia; Núcleo parabraquial lateral; Adenosina trifosfato; Receptores purinérgicos; Hipóxia; Lateral parabrachial nucleus; ATP; Purinergic receptors; Hypoxia; CIENCIAS BIOLOGICAS::FISIOLOGIA